2015
DOI: 10.1016/j.ejvs.2015.03.059
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Hemodialysis Reliable Outflow (HeRO) Graft for Haemodialysis Vascular Access

Abstract: This literature review shows that the HeRO graft is an acceptable option for complex dialysis patients who are catheter dependent. Owing to device availability, published data are predominantly North American and further longer-term studies in other populations may be necessary. In this challenging patient group, randomized controlled trials are required to allow comparisons with alternative access options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 18 publications
2
55
1
3
Order By: Relevance
“…Other complications associated with TDCs such as thrombosis, steal syndrome and ultimately, central venous stenosis and/or occlusion have also been reported to be significantly less for the HeRO graft [4], [6], [7]. Both Al Shakarchi et al and Katzman et al noted low incidences of steal syndrome with percentages reported as 6.3% and 2.6% respectively [4], [7].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Other complications associated with TDCs such as thrombosis, steal syndrome and ultimately, central venous stenosis and/or occlusion have also been reported to be significantly less for the HeRO graft [4], [6], [7]. Both Al Shakarchi et al and Katzman et al noted low incidences of steal syndrome with percentages reported as 6.3% and 2.6% respectively [4], [7].…”
Section: Discussionmentioning
confidence: 95%
“…A review of the literature suggests that rates of infection and bacteraemia associated with the HeRO graft are significantly less than those associated with TDCs and consequently, the rates of associated mortality are also less. A systematic review of the literature by Al Shakarchi et al report device related bacteraemia (per 1000 days) of 0.13-0.7 and HeRO graft infection in just 10.1% (2.5–21%) [4]. When compared with the reported catheter-related incidences, it is evident that these values are significantly lower for the HeRO graft than they are for TDCs.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations